Dual role of the mycobacterial cord factor TDM in cross-regulation of macrophage responses to IFN gamma - Killy, Barbara; Huber, Angelika; Ekici, Arif Bülent; Wirtz, Stefan; Dalpke, A.; Lang, Roland (2017)
EVALuna2:33888

Specific Lobar Affection Reveals a Rostrocaudal Gradient in Functional Outcome in Spontaneous Intracerebral Hemorrhage - Gerner, Stefan; Kuramatsu, Joji; Möller, Sebastian; Huber, Angelika; Lücking, Hannes; Kloska, Stephan; Madzar, Dominik; Sembill, Jochen; Schwab, Stefan; Huttner, Hagen (Stroke, 2017)
Several studies have reported a better functional outcome in lobar intracerebral hemorrhage (ICH) compared with deep location. However, among lobar ICH, a correlation of hemorrhage site-involving the specific lobes-with functional outcome has not been established.Conservatively treated patients with supratentorial ICH, admitted to our hospital over a 5-year period (2008-2012), were retrospectively analyzed. Lobar patients were classified as isolated or overlapping ICH according to affected lobes. Demographic, clinical, and radiological characteristics were recorded and compared among lobar ICH patients using above subclassification. Functional outcome-dichotomized into favorable (modified Rankin Scale, 0-3) and unfavorable (modified Rankin Scale, 4-6)-was assessed after 3 and 12 months. Multivariate regression analysis was performed to identify predictors for favorable outcome.Of overall 553 patients, 260 had lobar ICH. In isolated lobar ICH, median hematoma-volume decreased from rostral (frontal, 22.4 mL [7.3-55.5 mL]) to caudal (occipital, 7.1 mL [5.2-16.4 mL]; P=0.045), whereas the proportion of patients with favorable outcome increased (frontal: 23/63 [36.5%] versus occipital: 10/12 [83.3%]; P=0.003). Patients with overlapping lobar ICH had larger ICH volumes than isolated lobar ICH (overlapping, 48.9 mL [22.6-78.5 mL] versus 15.3 mL [5.0-44.6 mL]; P<0.001) and poorer clinical status on admission (Glasgow Coma Scale and National Institutes of Health Stroke Scale). Correlations with anatomic aspects provided evidence of a rostrocaudal gradient with increasing gray/white-matter ratio and decreasing hematoma-volume and rate of hematoma enlargement from frontal to occipital ICH location. Multivariate analysis revealed affection of occipital lobe (odds ratio, 3.75 [1.38-10.22]) and affection of frontal lobe (odds ratio, 0.52 [0.28-0.94]) to be independent predictors for favorable outcome and unfavorable outcome, respectively.Among patients with lobar ICH radiological and outcome characteristics differed according to location. Especially affection of the frontal lobe was frequent and associated with unfavorable outcome after 3 months.
EVALuna2:22482